Lasers in Pediatric Dentistry: A Review Article - Ankita Sinha1, Susant Mohanty2 , Sonu Acharya3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Laser applied science has been newly introduced into the dentistry to substitute drilling. The 1st dentalexperience for pediatric patients using laser can be useful from the point of preventive & therapeuticapproach. This article approached to educate about laser physics, its components, fundamentals, mechanismof its action, applications, advantages,disadvantages, laser safety & medico-legal aspects of laser specificallyconcerning pediatric dentistry. Due to their minimal invasion, treatment by laser is well accepted by children.The use of scalpels conventionally, may produce post-operative discomfort & thus, prolonged wound healing.Being safe in use, lasers are an important in-office alternative to treat pediatric dental patients. Hence, lasersuse enhances the children’s cooperation leading to greater satisfaction by all three i.e. guardians,patient &dentist.